2006
DOI: 10.4102/curationis.v29i2.1077
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve the performance of learners in a nursing college Part I: Issues pertaining to nursing education

Abstract: Three focus group interviews were conducted. One group was formed by seven tutors, and the other two groups were formed by fourth-year learners following a fouryear comprehensive diploma course. All participants voluntarily took part in the study. Data was analyzed using the descriptive method of open coding by Tesch (in Creswell, 1994:154-156). Trustworthiness was ensured in accordance with Lincoln and Guba’s (1985:290-326) principles of credibility, conformability, transferability and dependability.
Th…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…The current study findings correlate with findings of recent study conducted by Nuuyoma, Louw and Van der Merwe (2017) in the same setting, where the students identified a need for clinical mentors and proposed time allocation for clinical mentors in their timetable for provision of feedback. The above finding also concur with those from studies conducted by Cassimjee and Bhengu (2006), Waterson et al, (2006) and Maselele, Tjallinks and Norval (2001) who identified that nursing students were receiving inadequate clinical supervision, teaching and accompaniments, as clinical facilitators would stay for three months without doing clinical visits. Therefore, it was not surprising that the student respondents presented with high levels of stress due to limited teaching and supervision and the registered nurse's rejection of their teaching role in the wards.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…The current study findings correlate with findings of recent study conducted by Nuuyoma, Louw and Van der Merwe (2017) in the same setting, where the students identified a need for clinical mentors and proposed time allocation for clinical mentors in their timetable for provision of feedback. The above finding also concur with those from studies conducted by Cassimjee and Bhengu (2006), Waterson et al, (2006) and Maselele, Tjallinks and Norval (2001) who identified that nursing students were receiving inadequate clinical supervision, teaching and accompaniments, as clinical facilitators would stay for three months without doing clinical visits. Therefore, it was not surprising that the student respondents presented with high levels of stress due to limited teaching and supervision and the registered nurse's rejection of their teaching role in the wards.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…These statements raised the issue of a lack of sincerity about their education and apathetic attitudes among students. These findings concur with the findings of Waterson et al (2006) who maintain that students lack respect for their supervisors.…”
Section: Theme 2: Professional Nurses' Perceptions Of Values and Beliefs Of Studentssupporting
confidence: 91%
“…The integration of knowledge, skills, attitudes and values in a specified context is one of the cornerstones advocated by the outcomes-based approach to teaching nursing [3]. Such integration yields nurse tutor performance that must promote the professional care to patients.…”
Section: Introductionmentioning
confidence: 99%